IN-HOME-PD: The effects of longitudinal telehealth-enhanced interdisciplinary home visits on care and quality of life for homebound individuals with Parkinson's disease. (September 2022) - Fleisher, Jori E.; Hess, Serena P.; Klostermann, Ellen C.; Lee, Jeanette; Myrick, Erica; Mitchem, Daniela; Niemet, Claire; Woo, Katheryn; Sennott, Brianna J.; Sanghvi, Maya; Witek, Natalie; Beck, James C.; et al.
Abstract: Introduction: Homebound individuals with advanced Parkinson's disease (PD) are underrepresented in research and care. We tested the impact of interdisciplinary, telehealth-enhanced home visits (IN-HOME-PD) on patient quality of life (QoL) compared with usual care. Methods: Nonrandomized controlled trial of quarterly, structured, telehealth-enhanced interdisciplinary home visits focused on symptom management, home safety, medication reconciliation, and psychosocial needs (ClinicalTrials.gov NCT03189459). We enrolled homebound participants with advanced PD (Hoehn & Yahr (HY) stage ≥3). Usual care participants had ≥2 visits in the Parkinson's Outcomes Project (POP) registry. We compared within- and between-group one-year change in QoL using the Parkinson's Disease Questionnaire. Results: Sixty-five individuals enrolled in IN-HOME-PD (32.3% women; mean age 78.9 (SD 7.6) years; 74.6% white; 78.5% HY ≥ 4) compared with 319 POP controls, with differences in age, race, and PD severity (37.9% women; mean age 70.1 (7.8) years; 96.2% white; 15.1% HY ≥ 4). Longitudinally, the intervention group's QoL remained unchanged (within-group p = 0.74, Cohen's d = 0.05) while QoL decreased over time in POP controls (p < 0.001, Cohen's d = 0.27). The difference favored the intervention (between-group p = 0.04). POP participants declined in 7/8 dimensions while IN-HOME-PD participants' bodily discomfort improved and hospice use and death at home—markers of goal-concordant care—far exceeded national data. Conclusions: Telehealth-enhanced home visits can stabilize and may improve the predicted QoL decline in advanced PD via continuity of care and facilitating goal-concordant care, particularly among diverse populations. Extrapolating features of this model may improve continuity of care and outcomes in advanced PD. Highlights: Homebound people with Parkinson's disease are unrepresented in care and research. Underrepresented minorities with advanced Parkinson's may become homebound earlier. Interdisciplinary home visits maintain continuity compared with usual care. Home visits stabilized quality of life over one year versus decline in usual care. Home visits improved bodily discomfort in people with advanced Parkinson's.